Selection and promotion process to supervisory positions in Mexico, 2015 - López, José Guadalupe Hernández (Avances en Supervisión Educativa, 2015)
In Mexico it is starting a process of selection and promotion of teachers to supervisory positions through what has been called competitive examinations. This competition, derived from the Education Reform 2013, is justified by the alleged finding the best teachers to fill them. As a "new" process in the Mexican education system has led to a series of disputes since that examination was confined to the application and resolution of a standardized test consisting of multiple-choice questions applied in a session of eight hours which it determines whether a teacher is qualified or not qualified for the job.
Keywords: educative reform; management; school management; competitive exam